Electro-oxidation of 5-hydroxymethylfurfural by a catalyst containing copper nanoparticles and single copper atoms - Yongfang Zhou; Yi Shen; Hongying Li (Materials Today Catalysis, 2024)
Atomic-site electrocatalysts are being considered as potential alternative catalysts due to their exceptionally high atom utilization efficiencies, well-defined active sites and high selectivities. However, the presence of nanoparticles in the single-atom catalysts may affect the catalytic performance. Herein, single-copper-atoms and copper nanoparticles co-embedded in nitrogen-doped carbon nanosheets (CuNPs@Cu/NCNSs) were synthesized for 5-hydroxymethylfurfural electro-oxidation. Single copper atoms supported on nitrogen-doped carbon nanosheets (Cu/NCNSs) and copper nanoparticles supported on carbon (CuNPs/C) were also synthesized for comparison. The CuNPs/C exhibited high efficiency in electro-oxidation of HMF to 2,5-furandicarboxylic acid (FDCA) at a low potential of 1.42 V. However, the CuNPs@Cu/NCNSs showed a high 5-formyl-2-furancarboxylic acid (FFCA) selectivity of 86.7%. Oxalic acid (OA) treatment experiments showed that single copper atoms played a major role on the oxidation of HMF to FFCA. Cu(OH)2 active species generated by electrochemical oxidation were demonstrated as the primary catalytic sites for HMF oxidation on the CuNPs/C. In-situ Raman spectra results demonstrated that HMF oxidation on the CuNPs/C followed the path to 5-hydroxymethyl-2-furancarboxylic acid (HFCA), while on the CuNPs@Cu/NCNSs and Cu/NCNSs, HMF was oxidized along the 5-diformylfuran (DFF) pathway.